Influence Of Perceived Usefulness, Perceived Ease Of Use And Social Influence On Behavioral Intention To Use Of E-Hailing Applications In Padang City: A Review Based On The Technology Acceptance Model Approach - Nadia Putri Winata; Perengki Susanto (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the ease of use of e-hailing applications in Padang City using the Technology Acceptance Model approach. The population in the study were people living in Padang City who had the E-Hailing Application on their mobile phones and the number of samples in this study was 280 respondents. The research method used was quantitative with data collection through online questionnaires. Data analysis was carried out using SmartPLS 4.0.9.9 software. The results of this study indicate that: (1) Perceived Ease of Use has a positive and significant effect on Perceived Usefulness. (2) Perceived Usefulness has a positive and significant effect on Behavioral Intention to use. (3) Perceived Ease of Use has a positive and significant effect on Behavioral Intention to use. (4) Social Influence has a positive and significant effect on Behavioral Intention to use. This study concludes that benefits, ease of use, and social influence are important factors in driving the adoption of e-hailing services. These results can be a basis for application developers and policy makers in designing strategies that are more adaptive to local user needs and behavior.